2016
DOI: 10.3847/2041-8205/830/1/l10
|View full text |Cite
|
Sign up to set email alerts
|

Smash 1: A Very Faint Globular Cluster Disrupting in the Outer Reaches of the Lmc?

Abstract: We present the discovery of a very faint stellar system, SMASH 1, that is potentially a satellite of the Large Magellanic Cloud. Found within the Survey of the MAgellanic Stellar History (SMASH), SMASH 1 is a compact ( r 9.1 pc h 3.4 5.9) and very low luminosity ( M) stellar system that is revealed by its sparsely populated main sequence and a handful of red giant branch candidate member stars. The photometric properties of these stars are compatible with a metal-poor ( Fe H 2.2 [ ] ) and old (13 Gyr) isochron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Among the 123 globular clusters presented here, the properties of 116 were extracted from Harris (1996) catalog, revised in 2010. For the remaining ones (Kim 1, Kim 2, Kim 3, Laevens 1, Balbinot 1, Munoz 1 and SMASH 1) parameters of the discovery publications were used , , Kim et al (2016), Laevens et al (2014), Balbinot et al (2013), Muñoz et al (2012) and Martin et al (2016b)). Globular cluster metallicity spread measurements are taken from Willman & Strader (2012) and references therein: Carretta et al (2006, 2011), Cohen et al (2010, Gratton et al (2007), Johnson & Pilachowski (2010), and Marino et al (2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 123 globular clusters presented here, the properties of 116 were extracted from Harris (1996) catalog, revised in 2010. For the remaining ones (Kim 1, Kim 2, Kim 3, Laevens 1, Balbinot 1, Munoz 1 and SMASH 1) parameters of the discovery publications were used , , Kim et al (2016), Laevens et al (2014), Balbinot et al (2013), Muñoz et al (2012) and Martin et al (2016b)). Globular cluster metallicity spread measurements are taken from Willman & Strader (2012) and references therein: Carretta et al (2006, 2011), Cohen et al (2010, Gratton et al (2007), Johnson & Pilachowski (2010), and Marino et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…We use our MC photometry to refine the structural properties of Sgr II previously studied by L15 and M18 and determine its main stellar properties through a CMD and spatial distribution fitting procedure. The formalism of this analysis is detailed in Martin et al (2016a) and L18. Though the main steps will be briefly detailed below, we refer the reader to these two references for more details.…”
Section: Structural and Cmd Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…We preferred those reprojected images which have been corrected for distortion, etc, and are better astrometrically fixed. Finally, we filtered g images with exposure times longer than 267 sec; the deepest images obtained by the DECam (Martin et al 2016;Drlica-Wagner et al 2016;Kim et al 2016). Then we run the DAOFIND routine within the DAOPHOT suite of programs (Stetson et al 1990) to produce photometric catalogs of each ∼ 2.2 deg FOV image down to g ∼ 24.0 mag.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…As stellar clusters are considered, some recent outcomes have shown that there are still a substantial number of extreme low luminosity stellar clusters undetected in the wider MS periphery and the MW halo (Kim et al 2015;Pieres et al 2016;Martin et al 2016). Furthermore, streams of gas and stars that might harbor stellar clusters have also been detected Belokurov et al 2016;Deason et al 2016).…”
Section: Introductionmentioning
confidence: 99%